2016
DOI: 10.1249/mss.0000000000000780
|View full text |Cite
|
Sign up to set email alerts
|

Do Basketball Players Have a High Risk of Pulmonary Embolism? A Scoping Review

Abstract: Basketball players seem to have a higher risk of PE than their peers from the general population. More studies are needed to confirm these findings and identify factors predisposing them to PE to contribute to its prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Increase of АМо duration of RR-intervals and IT witness about tonus increase of sympathetic sector. Increase of variation range of RR-intervals' duration witnesses about increase of para-sympathetic sector's influence [9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increase of АМо duration of RR-intervals and IT witness about tonus increase of sympathetic sector. Increase of variation range of RR-intervals' duration witnesses about increase of para-sympathetic sector's influence [9].…”
Section: Methodsmentioning
confidence: 99%
“…Deficit of athletes' individual features' consideration can also lead to risk of different diseases. Casals et al [9] showed that there is high risk of pulmonary embolism in basketball players. The authors found that in average frequency of such disease are 1.27 and 2.06 cases per 1000 players in year.…”
mentioning
confidence: 99%
“…A total of 55 VTEs were identified in online records from 1999 through 2016. Twenty-two events occurred in NHL players ( Table 1 ), 16 in MLB players ( Table 2 ), 12 in NFL players ( Table 3 ), and 5 in NBA players 6 ( Table 4 ). Nineteen athletes were reported to have an upper extremity DVT, 15 had a lower extremity DVT, 15 had a PE, and 6 had a DVT with PE.…”
Section: Resultsmentioning
confidence: 99%
“…Only 1 article was identified through the PubMed and SPORTDiscus search; that article identified 3 NBA players with PE who were already included from the Google search, and the remainder of athletes included were from reports from the Google search. 6 This may have resulted in a selection bias, such that our study included high-profile professional athletes with access to high levels of medical care and intense media attention. Therefore, our study likely underestimated the true incidence of VTE given that an unknown number of athletes may have been missed.…”
Section: Discussionmentioning
confidence: 99%
“…Although athletes are typically thought to be lower risk for thromboembolic disease given their elevated activity levels and perception of peak physical fitness, they are often exposed to thrombogenic risk factors that have been shown to make them more susceptible. 6 Virchow's triad classically reduces VTE risk factors into three broad categories: hypercoagulability; endothelial damage; and venous stasis. 7 Athletes are subject to risk factors in all three categories.…”
Section: Discussionmentioning
confidence: 99%